Implementation of the government regulatory improvement of Colima - Vargas-Hernández, José G.; Díaz Laureano, Irma Yolanda (Estado, Gobierno y Gestión Pública, 2014)
The objective concerns demonstrate the importance of studying the implementation of programs of regulatory reform in the government of the state of Colima, is to identify the degree of fulfillment of the objectives in the implementation, the proposed method is the documentreview, ethnography and interviews, as main conclusion shows that this information is highly relevant because it shows data for a successful public policy that translates into benefits for society and the competitiveness ofthe state.